Biologically inspired dexterous robot hand actuated by smart material based artificial muscles - Price, Aaron David (University of Ottawa (Canada), 2006)
Modern externally powered upper-body prostheses are conventionally actuated by electric servomotors. Although these motors achieve reasonable kinematic performance, they are voluminous and heavy. Deterring factors such as these lead to a substantial proportion of upper extremity amputees avoiding the use of their prostheses. Therefore, it is apparent that there exists a need for functional prosthetic devices that are compact and light-weight. The realization of such a device requires an alternative actuation technology, and biological inspiration suggests that tendon based systems are advantageous. Shape memory alloys are a type of smart material that exhibit an actuation mechanism resembling the biological equivalent. As such, shape memory alloy enabled devices promise to be of major importance in the future of dexterous robotics, and to prosthetics in particular. This thesis investigates the issues surrounding the practical application of shape memory alloys as artificial muscles in a three fingered robot hand. First the function of the human hand and the kinematic requirements for manipulation are reviewed. An overview of artificial hands is provided, followed by a discussion on shape memory alloys focused on the unique phenomena of the shape memory effect. Second, the forward and inverse kinematics of the artificial finger are established in order to relate the desired finger tip contact point to the required joint angles. This is followed by the design of the requisite instrumentation and control systems. Due to the highly nonlinear nature of both the SMA and the robot hand, alternative control approaches such as neural networks are reviewed. Finally, a large-strain SMA actuator is proposed and the concepts explored herein are applied to the design, manufacture, and evaluation of an SMA actuated robotic hand.
Keywords: Engineering, Mechanical.; Engineering, Robotics.